Sleep Disorders and Fatigue among Health Care Providers Working at University Hospitals - Nasim Tabrizi; Athena Sharifi Razavi; Mitra Alizadeh (Journal of Sleep Sciences, 2020)
Background and Objective: Sleep disorder and fatigue are common among health care workers (HCWs) and negative-ly affect their quality of life and caregiving to the patients. Early diagnosis and rapid modification of causative factors might prevent the potential disastrous results of these problems on personal and population health. This study aimed to evaluate the state of sleep and fatigue among HCWs of hospitals affiliated to Mazandaran University of Medical Sci-ences, Iran, and their related factors. Materials and Methods: This cross-sectional study was conducted from September 2014 to December 2014 among HCWs at hospitals of Mazandaran University of Medical Sciences. Demographic data, medical history, and occupation-al shift information were recorded. Sleep quality was assessed by the valid and reliable Persian versions of Insomnia Severity Index (ISI) and Pittsburgh Sleep Quality Index (PSQI). Fatigue was evaluated by valid and reliable Persian version of Fatigue Severity Scale (FSS). Statistical analysis was performed using SPSS software. Results: 595 HCWs participated in the study. According to ISI, 48.4% of HCWs experienced subthreshold insomnia, 25.4% were affected by moderate, and 5.0% by severe clinical insomnia. PSQI indicated poor sleep quality in 79.8% of the participants. 71.6% of HCWs had FSS of 4 or more, which was correlated to gender, age, and sleep quality. Correla-tion of sleep quality components with participants’ shift characteristics was also investigated. Conclusion: Sleep disorders and fatigue are common in HCWs of university hospitals. Correction of certain modifiable factors can reduce negative consequences of sleep disorders and fatigue in HCWs.